An analysis of how restrictive language policies are interpreted by Arizona's Department of Education and three individual school districts' websites - Margarita Jimenez-Silva; Katie Bernstein; Evelyn Baca (Arizona State University, 2016)
Restrictive language policies for education have been passed in several states in the United States. In 1998, 2000, and 2002, California, Arizona, and Massachusetts passed the most restrictive of these policies, impacting 4.4 million students classified as English language learners (ELLs). This study examines how these policies are currently interpreted and presented to the public on Arizona's Department of Education website, as well as how they are interpreted and presented on the websites of three of the state's largest school districts. We seek to understand how three key elements of the laws-one-year programmatic time limits, Structured English Immersion (SEI) programs, and waiver processes-are conveyed by each text. Using tools from critical discourse analysis (Fairclough, 2003, 2013, 2015), we trace the endurance or disappearance of these elements between texts and across time. Textual differences are discussed as reflecting and perpetuating important contextual differences among the districts.